Advances in HIV diagnosis and monitoring. (3rd July 2020) - Kabir, Md Alamgir; Zilouchian, Hussein; Caputi, Massimo; Asghar, Waseem
Abstract: Although highly active antiretroviral therapy (HAART) has been introduced over twenty years ago to treat Human Immunodeficiency Virus (HIV) positive patients, acquired immunodeficiency syndrome (AIDS) is still one of the deadliest diseases found worldwide. AIDS prevalence and mortality rates are usually more pronounced in resource-constrained countries than in the developed world. The lack of trained medical technicians, sophisticated diagnostic equipment, and the overall scarcity of medical infrastructures have severely impacted HIV/AIDS diagnostics, which hinders the initiation and periodic monitoring of antiretroviral therapy (ART). Currently, available HIV viral load assays are not well-suited for resource-limited settings due to their high cost and a requirement for medical/technical infrastructures. In this paper, we review current and emerging diagnostic assays for HIV detection, with a focus on point-of-care (POC) based immunoassays for viral load measurement, drug resistance, and HIV recurrence. We also discuss the limitations of the available HIV assays and highlight the technological advancements in cellphone, paper, and flexible material-based assays which have the potential to improve HIV diagnosis and monitoring, thus assisting with the management of the disease.